A 31.5 GHz Patch Antenna Design for Medical Implants. (8th September 2008) - Ahmed, Yasir; Hao, Yang; Parini, Clive
Abstract : We have proposed a 31.5 GHz patch antenna for medical implants. The design is based on the transmission line model and is simulated in CST. The patch antenna performs reasonably well in terms of return loss and radiation efficiency. However, the most attractive feature of this design is its form factor. Typical antennas designed for the microwave range are quite large in size, which makes them unsuitable for implants. The proposed design is much smaller in size but still retains the essential characteristics for reliable communication.